Scientists' perspectives on global ocean research priorities - Rudd, Murray A. (Frontiers in Marine Science, 2014)
Diverse natural and social science research is needed to support policies to recover and sustain healthy oceans. While a wide variety of expert-led prioritization initiatives have identified research themes and priorities at national and regional scale, over the past several years there has also been a surge in the number of scanning exercises that have identified important environmental research questions and issues “from the bottom-up.” From those questions, winnowed from thousands of contributions by scientists and policy-makers around the world who participated in terrestrial, aquatic and domain-specific horizon scanning and big question exercises, I identified 657 research questions potentially important for informing decisions regarding ocean governance and sustainability. These were distilled to a short list of 67 distinctive research questions that, in an internet survey, were ranked by 2179 scientists from 94 countries. Five of the top 10 research priorities were shared by respondents globally. Despite significant differences between physical and ecological scientists' priorities regarding specific research questions, they shared seven common priorities among their top 10. Social scientists' priorities were, however, much different, highlighting their research focus on managerial solutions to ocean challenges and questions regarding the role of human behavior and values in attaining ocean sustainability. The results from this survey provide a comprehensive and timely assessment of current ocean research priorities among research-active scientists but highlight potential challenges in stimulating crossdisciplinary research. As ocean and coastal research necessarily becomes more transdisciplinary to address complex ocean challenges, it will be critical for scientists and research funders to understand how scientists from different disciplines and regions might collaborate and strengthen the overall evidence base for ocean governance.